2012
DOI: 10.1007/s10900-012-9541-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Prevalence and Barriers of HBV Screening and Vaccination Among Asian Americans

Abstract: Our study identifies the prevalence of HBV virus (HBV) screening and vaccination among Asian Americans, and ethnic differences for factors associated with screening and vaccination behaviors. In 2009–2010 we recruited 877 Korean, Chinese, and Vietnamese Americans 18 years of age and above through several community organizations, churches and local ethnic businesses in Maryland for a health education intervention and a self-administered survey. Prevalence of HBV screening, screening result and vaccinations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 28 publications
6
54
1
Order By: Relevance
“…Few other Asian American studies have examined level of education as a factor associated with the prevalence of anti-HBc. Consistent with previous studies (14,27), our study significantly correlated level of education with chronic HBV infection among Asian Americans. The inadequate apparatus of disease control and screening and vaccination policy in the origin countries resulted in hepatitis B infection-related health disparity among individuals with different educational levels.…”
Section: Discussionsupporting
confidence: 92%
“…Few other Asian American studies have examined level of education as a factor associated with the prevalence of anti-HBc. Consistent with previous studies (14,27), our study significantly correlated level of education with chronic HBV infection among Asian Americans. The inadequate apparatus of disease control and screening and vaccination policy in the origin countries resulted in hepatitis B infection-related health disparity among individuals with different educational levels.…”
Section: Discussionsupporting
confidence: 92%
“…The first basic model included demographic variables: age, sex, US residency, educational attainment, self-reported English-speaking ability, and health insurance coverage, which were significantly associated with HBV screening in previous studies. 8,14,25 The second regression model added the variable of physician's recommendation for cancer. The third model added the HBV knowledge variable.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers found that VA immigrant women with limited English literacy skills, lower educational levels, and financial barriers were less likely to have cancer vaccine acceptance and believe in being susceptible to developing CC (Strong, Lee, Tanaka, & Juon, 2012;Yi et al, 2013). VA immigrant women who reported respect for their health care provider (HCP)s' opinions were more likely to accept medical recommendations for cancer prevention vaccinations (Strong et al, 2012;Yi et al, 2013).…”
Section: )mentioning
confidence: 99%